The Effectiveness of Fertilization Based on Nutrient Requirements and the Production Target of Green Cawri (Brassica Juncea. L) In a Hydroganic System - Lutfi Henderlan Harahap (International Journal of Educational Technology and Society, 2024)
This research aims to evaluate the effectiveness of fertilization based on nutrient requirements and production targets of green mustard (Brassica juncea. L) in a hydroponic system. The study involved varying fertilizer dosages and integrating them into the hydroponic system to assess the growth and production of mustard plants. The results showed that increasing fertilizer dosages in line with production targets could enhance plant growth, such as plant height, leaf count, and leaf width, as well as plant production in terms of wet and dry weights. Integrating fertilizer dosages with the hydroponic system also demonstrated increased effectiveness of fertilization on the growth and production of mustard plants. The interaction between increasing fertilizer dosages and the hydroponic system also positively impacted mustard plant production. The role of the hydroponic system in improving the efficiency of complete fertilizer application in mustard cultivation was evidenced by an increase in production yields of up to 24 tons/ha. These findings indicate that adjusting fertilizer dosages to match plant nutrient requirements and integrating them with a hydroponic system can enhance the growth and production of green mustard plants under hydroponic conditions.